Dopamine receptor D5 deficiency results in a selective reduction of hippocampal NMDA receptor subunit NR2B expression and impaired memory. (April 2016) - Moraga-Amaro, Rodrigo; González, Hugo; Ugalde, Valentina; Donoso-Ramos, Juan Pablo; Quintana-Donoso, Daisy; Lara, Marcelo; Morales, Bernardo; Rojas, Patricio; Pacheco, Rodrigo; Stehberg, Jimmy
Abstract: Pharmacological evidence associates type I dopamine receptors, including subtypes D1 and D5, with learning and memory. Analyses using genetic approaches have determined the relative contribution of dopamine receptor D1 (D1R) in cognitive tasks. However, the lack of drugs that can discriminate between D1R and D5R has made the pharmacological distinction between the two receptors difficult. Here, we aimed to determine the role of D5R in learning and memory. In this study we tested D5R knockout mice and wild-type littermates in a battery of behavioral tests, including memory, attention, locomotion, anxiety and motivational evaluations. Our results show that genetic deficiency of D5R significantly impairs performance in the Morris water maze paradigm, object location and object recognition memory, indicating a relevant role for D5R in spatial memory and recognition memory. Moreover, the lack of D5R resulted in decreased exploration and locomotion. In contrast, D5R deficiency had no impact on working memory, anxiety and depressive-like behavior, measured using the spontaneous alternation, open-field, tail suspension test, and forced swimming test. Electrophysiological analyses performed on hippocampal slices showed impairment in long-term-potentiation in mice lacking D5R. Further analyses at the molecular level showed that genetic deficiency of D5R results in a strong and selective reduction in the expression of the NMDA receptor subunit NR2B in the hippocampus. These findings demonstrate the relevant contribution of D5R in memory and suggest a functional interaction of D5R with hippocampal glutamatergic pathways. Graphical abstract: Highlights: Dopamine receptor D5 (D5R) deficiency results in impaired learning and spatial memory. Genetic deficiency of D5R results in impaired synaptic plasticity. D5R deficiency results in attenuated expression of hippocampal NMDA subunit NR2B.